Plasma activated coatings with dual action against fungi and bacteria. (September 2018) - Akhavan, Behnam; Michl, Thomas D.; Giles, Carla; Ho, Kitty; Martin, Lewis; Sharifahmadian, Omid; Wise, Steven G.; Coad, Bryan R.; Kumar, Naresh; Griesser, Hans J.; Bilek, Marcela M.
Graphical abstract: Highlights: An effective coating-strategy for killing fungi and bacteria before they can settle on the surface. Radical-rich plasma poylmerized (PP) films are deposited on titanium surfaces. The embedded radicals are utilized to covalently bind antimicrobial peptides, Mel4 or caspofungin. Both C. albicans and S. aureus pathogens were inhibited in their ability to colonize the surfaces. Abstract: In the oral cavity, dental implants are exposed to an environment rich in various microbes that can produce infectious biofilms on the implant surface. Here we report the development of two distinct antimicrobial coatings that prevent biofilm formation by fungi or bacteria. The antimicrobial peptides Mel4 and caspofungin were immobilized on titanium surfaces through reactions with radicals embedded within a mechanically robust, ion-assisted plasma polymerized (PP) film. The immobilization does not require additional chemical reagents and is achieved by simply incubating the surfaces at room temperature in a buffer solution containing the antimicrobial agent. The antibiotic-functionalized surfaces were rigorously washed with hot sodium dodecyl sulphate (SDS) to remove physisorbed molecules, and analyzed by time of flight secondary ion mass spectrometry (ToF-SIMS), which revealed characteristic fragments of the peptides and provided strong evidence for the covalent nature of the binding between the molecules and the PP coating. Both Candida albicans and Staphylococcus aureus pathogens were significantly inhibited in their ability to colonize the surfaces and form biofilms. Our findings suggest that antimicrobial surfaces fabricated using ion-assisted plasma polymerization have great potential for coatings on biomedical devices where activity against fungal and bacterial pathogens is required.